Efeito do clareamento dental na resistência de união de sistemas adesivos ao esmalte - Steglich, Ana Guerreiro (2014)
With the increasing demand of the population for dental bleaching and concomitant evolution of adhesive systems, has increasingly sought to know more about the relationship between bleaching and esthetic restorations. Because of that this work aims to evaluate the influence of in-office bleaching challenge the bond strength of adhesive systems to dental enamel. To this were randomly divided 40 permanent human molars were divided into 4 groups (n = 10) teeth in accordance with the Single Bond (3M ESPE) and Universal Single Bond (3M ESPE) and treatment (bleaching and whitening without). The teeth were prepared and had their root surface removed in the transverse direction with diamond disk, the coronal portion was sectioned along the axis of the tooth in the mesial - distal direction, resulting in two sections, which were embedded in acrylic resin in PVC rings, the eixar mode exposed enamel surface. The smooth surfaces were ground with 600-grit sandpaper under water cooling, so you obtain a flat surface. On the surface enamel adhesive system according to the group indicated and in accordance with the manufacturers recommendations was applied and after that the adhesive was light cured for 10 seconds. After light curing of the adhesive was a cylinder made of composite resin, with dimensions of 2.0 x1, 09mm, with the aid of an all perforated starch. The specimens of groups with whitening underwent 2 sessions of office bleaching with carbamide peroxide gel 37 % with an interval of 7 days between them. After that were stored in a thermal oven at 37 º C for 24h and then the mechanical test microshear was performed to measure the bond strength. Have the groups without bleaching were stored in a thermal oven 37 º C for 24h and then subjected to testing microshear. The data relating to test microshear, expressed in MPa, were subjected to statistical analysis. The sampling distribution of the data was assumed to follow normal after completion of the Kolmogorov - Smirnov test. The values of bond strength in MPa were subjected to analysis of variance of two factors in order to check the influence of the bleaching procedure after challenge adhesive and adhesive system. The significance level for all analyzes was 5% and these were performed in Minitab 17 software (Minitab Inc., State College, PA, USA). Analysis of variance was not able to point to significant differences factors prior treatment with acid or with self-etching adhesive conditioning. As for tooth whitening there were no significant differences (p = 0.272) .Also there were no significant differences in the adhesive system employed , SBU or BSA (p = 0.187) nor for the interaction between the two factors (p = 0.758 ) . So the thooth whitening is a safe procedure in this conditions.